The Correlation Between Social Media Usage and Imposter Syndrome Among College Students in Islamabad: Exploring the Role of Class Level (HSSC 1, HSSC 2) Differences - Bareeha Kamran; Afia Misri; Ayesha Nadeem; Izah Shafqat; Eisha Tir Radia Shahbaz; Rubab Khan (Research Journal of Psychology, 2025)
In today’s digital age, academic meritocracy dictates self-worth creating fertile ground for the proliferation of Imposter Syndrome - a psychological phenomenon characterized by pervasive feelings of fraudulence and incompetence, despite evident accomplishments. Global research suggests that multiple sociocultural factors play a role in the development of this pressing psychological struggle, among which social media usage is of notable importance. Social media usage can either amplify self-doubt, or reduce it by providing emotional support and reassurance. This study aims to examine the intricacy of this relationship among Pakistani college students. A quantitative cross-sectional design was adopted, and data was collected from a sample of 300 first-and second-year college students in Islamabad through convenience sampling. A statistically significant correlation between imposter syndrome and Social media usage was reported, however, individual differences were also observed. This study offers a critical, empirically grounded perspective on imposter syndrome in Pakistan, bridging the fields of developmental psychology, digital behavior, and sociocultural research. It informs of the need to curate culturally adaptive interventions designed to proactively manage this phenomenon before its full-blown manifestation in an era where academic excellence and online validation are deeply intertwined.